Profile of Children with Congenital Heart Disease and Upper Respiratory Tract Infection in Dr. Soetomo General Hospital Surabaya Period March 2018 - Izzati, Nabila; Rahman, Mahrus; Thirthaningsih, Ni Wayan (Universitas Airlangga, 2019)
Introduction: Congenital Heart Disease (CHD) is the leading cause of death in the first year of life. One of the manifestations of CHD is upper respiratory infection (URI). In Indonesia, 90% of the acute respiratory infection is URI and it becomes the most common reason for children to go to emergency center. The aim of this study is to describe the profile of children with congenital heart disease and upper respiratory tract infection (URTI) in Dr. Soetomo General Hospital, Surabaya, based on sex, age, immunization status, social-economic status, and type of CHD. Methods: This descriptive study was done by collecting data using medical records and questionnaires from March 1st to 31st 2018. Results: Total number of the sample was 46 patients; 18 (39.1%) of them were male and 28 (60.9%) were female, with male to female ratio was 1:1.6. The most common age group (69.6%) was toddler (0-5 years old). The most common type of CHD was acyanotic (89.1%). Conclusion: Female patients had more (80%) severe URI than male patients. Patients with severe URI only occur in toddlers. Interestingly, 60% of patients with severe URI had complete immunization. Patients with severe URI had parents with moderate (60%) and low income (40%). There were 100% of patients with severe URI who had acyanotic CHD.